Menumbuhkan Jiwa Kewirausahaan Sejak Dini dengan Memotivasi dan Melatih Keterampilan untuk Siswa MTs Negeri 1 Yogyakarta - Anas Hidayat; Asmai Ishak; Albari Albari; Febriani Wahyusari Nurcahyanti; Budi Setiono (Rahmatan Lil 'Alamin Journal of Community Services, 2023)
Community service is currently aimed at students at MTs Negeri 1 Yogyakarta, which aims to instill entrepreneurial insights, as well as foster and enhance an entrepreneurial spirit. Having an entrepreneurial spirit is an important point for the provision of students in the future. Apart from that, from this activity it is hoped that students can help the family economy and can also take advantage of their free time to carry out positive activities by way of entrepreneurship and minimize juvenile delinquency. This service activity was held on January 28, 2023 at the hall of MTs Negeri 1 Yogyakarta, with the title: "Entrepreneurship Education and Training to Make Dishwashing Liquid Soap for MTs Negeri 1 Yogyakarta students". The method used in this service activity is seminars as well as direct training as an effort to foster an entrepreneurial spirit and train the skills of MTs Negeri 1 Yogyakarta students in making dish soap. The results of the service activities showed that the participants had high enthusiasm for participating in this service event as well as being able to move the entrepreneurial spirit of the participants so that they had the attraction to try to become entrepreneurs in the future.